Produktywność pracy przedsiębiorstw prywatnych w Polsce – ujęcie regionalne: Labour productivity of private companies in Poland – regional approach - Wierzbicka, Wioletta (Management and Administration Journal, 2021)
The article presents the results of research on the regional differences in the labour productivity of private companies in Poland, and the changes that were occurring in this area in the years 1999-2011. The results of the analysis can be summarized as follows. In the years 1999-2011, the level of labour productivity of researched companies increased in all regions, and the regional differences in this area were reduced. In the population of voivodships, the processes of the internal convergence and divergence, including a nature of marginalization were observed. As a result of the changes, the lowest level in the labour productivity ranking, occupied in 2011, were the voivodships such as: Warmińsko-Mazurskie, Podkarpackie, Łódzkie and Lubelskie. Mazovieckie voivodship took the highest place in this ranking, which at the beginning of this period was characterized by a nearly 2-fold higher level of labour productivity than the rest of the voivodships.